Políticas indígenas e o ser indígena na Assembleia Nacional Constituinte - Santos, Ivan Pereira Rodrigues dos (2021)
This study aimed to analyze the construction of the indigenous identity and the policies undertaken by the Brazilian indigenous movement presented in the Brazilian National Constituent Assembly between 1987 and 1988, which contributed directly to the elaboration of the 1988 Brazilian Constitution. We seek to understand who the people who formed that movement were; and who the Indigenous leaders of different ethnicities and regions of Brazil responsible for building a supra-ethnic identity that gave cohesion to the social movement were. Besides, placing this study in the historiographical line called New Indigenous History was one of the objectives. That led to inserting theoretical elements from anthropology to understand both the ethnic phenomenon and the construction of the identity made by those indigenous leaders. In addition, compilations produced by jurists helped to understand the Brazilian laws and their transformations. The analysis of periodical publications from Porantim newspaper, minutes of sessions and audiences of the Constituent Assembly, and speeches by different Indigenous leaders in those subcommittee audiences built the object of this investigation. The documents produced and officially presented by Indigenous and indigenist organizations, such as the Proposals and Amendments on Indigenous peoples to the text of the Brazilian Constitution, were also analyzed